Isolation, identification and characterisation of Pseudomonas koreensis CM-01 isolated from diseased Malaysian mahseer (Tor tambroides) - Melinda Lau, Mei Lin; Cindy Kho, Jia Yung; Chung, Hung Hui; Azham, Zulkharnain (Elsevier B.V., 2024)
Pseudomonas species are one of the most threatening fish pathogens which reside a wide range of environments. In this study, the dominant bacteria were isolated from diseased Malaysian mahseer (Tor tambroides) and tentatively named CM-01. It was identified as Pseudomonas koreensis based on its biochemical, morphological, genetic and physiological information. Its pathogenicity was found to be correlated with twelve virulence genes identified including iron uptake, protease, acylhomoserine lactone synthase gacS/gacA component regulation system, type IV secretion system, hydrogen cyanide production, exolysin, alginate biosynthesis, flagella and pili. The median lethal dose (LD50) for the CM-01 isolate on Malaysian mahseer was documented at 5.01 × 107 CFU/mL. The experimental infection revealed that CM-01 led to significant histological lesions in the fish, ultimately resulting in death. These lesions comprise necrosis, tissue thickening and aggregation. Drug sensitivity tests had shown its susceptibility to beta-lactam combination agents and further suggest its drug of choice. Its growing features had shown its growth at optimal temperature and pH. To the best of our knowledge, this is the first report of P. koreensis linked to diseased T. tambroides.